From Early Strengths to Lifespan Well-Being: The Sequential Role of Resilience and Psychological Flexibility in a Turkish Post-Disaster Context - Maral, Sibel; Satici, Seydi Ahmet (SPRINGER, 2025)
The 2023 Kahramanmara & scedil;-Hatay earthquakes caused widespread collective trauma across T & uuml;rkiye, affecting both directly and indirectly exposed populations. This crisis underscored the urgent need to understand psychological factors that foster resilience and mental well-being in disaster-affected groups. Positive childhood experiences (PCEs) are key developmental assets that shape mental health across the lifespan. Yet, the mechanisms through which these early relational strengths influence adult well-being, particularly in non-Western and ecologically disrupted contexts, remain underexplored. Drawing on resilience theory and psychological flexibility frameworks, this study tested a serial mediation model in which resilience and psychological flexibility sequentially mediate the relationship between PCEs and adult mental well-being. Data were collected from 952 adults (91.5% female; Mage = 39.48, SD = 8.71, range = 18-66) across 75 Turkish cities in the post-earthquake period, offering a unique context to examine protective psychological mechanisms under macro-level adversity. Structural equation modeling confirmed the hypothesized model, revealing significant indirect effects of PCEs on mental well-being through both resilience and psychological flexibility. This study contributes to the literature by (1) offering a dynamic, process-oriented framework explaining how early developmental strengths promote adult mental health; (2) extending resilience theory to a national post-disaster context, emphasizing how early assets buffer against collective trauma; and (3) broadening positive psychology research through a socioeconomically and geographically diverse Turkish sample. The findings underscore the importance of culturally sensitive interventions that strengthen early relational resources and promote adaptive psychological capacities to sustain lifelong mental well-being.
Keywords: Positive childhood experiences; Resilience; Psychological flexibility; Mental well-being; T & uuml; rkiye; Post-disaster context; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH; POSITIVE PSYCHOLOGY; GROWTH; MINDFULNESS; PREVALENCE; SURVIVORS; EARTHQUAKE; PEOPLE; MODEL; Psychiatry